2019
DOI: 10.3391/mbi.2019.10.3.02
|View full text |Cite
|
Sign up to set email alerts
|

Between the hammer and the anvil: how the combined effect of global warming and the non-native common slider could threaten the European pond turtle

Abstract: Ballast water is a leading vector for the introduction of aquatic invasive species worldwide and, once a novel species is established, regional ballast water exchange between ports can accelerate secondary spread. The importance of shipping induced invasions in the Laurentian Great Lakes has resulted in policies that require more stringent ballast water treatment standards for transoceanic shipping than is required of ships operating regionally within the Great Lakes. As a result, ballast water discharges with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 38 publications
(50 reference statements)
0
21
0
Order By: Relevance
“…Invasive alien species (IAS) are a topic of major importance in many research areas, because of the countless implications they have on environment and human activities. IAS can alter ecosystem functioning by replacing, competing, or directly preying upon native species [1,2,3,4]. IAS can have a detrimental impact on agriculture, livestock farming, and, sometimes, human health [5,6,7], with significant impacts in terms of both social and economic costs for managing strategies [8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Invasive alien species (IAS) are a topic of major importance in many research areas, because of the countless implications they have on environment and human activities. IAS can alter ecosystem functioning by replacing, competing, or directly preying upon native species [1,2,3,4]. IAS can have a detrimental impact on agriculture, livestock farming, and, sometimes, human health [5,6,7], with significant impacts in terms of both social and economic costs for managing strategies [8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Further, all predictors were projected into an Equal Area Projection (WGS84 -Cylindrical Equal Area), to correct for any latitudinal bias (Brown, 2014); spatial jack-knife was set at 5 replicates per parameter and 3 spatial groups were created. Models were calibrated for both primary and secondary range localities of this species, a technique used to improve performance of predictions and reduce uncertainties (Broennimann & Guisan, 2008) when modelling the distribution of invasive species (Cerasoli et al, 2019;Iannella et al, 2019a;Perret et al, 2019;RodrĂ­guez-Rey et al, 2019).…”
Section: Ecological Niche Modellingmentioning
confidence: 99%
“…The ongoing climate change is one of the most important phenomena shaping the current distribution of species, of both conservation and invasive concern (Bellard et al, 2012;Cerasoli et al, 2019;Wieczynski et al, 2019). The spread of invasive species of all taxa has increased during the last few decades (Seebens et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Wildfires are currently one of the most important environmental problems as they cause disturbances in ecosystems generating environmental, economic and social costs (Viana-Soto et al 2017). In recent years, Geographic Information System (GIS) techniques are more and more used for biodiversity conservation and human impact issues (Dominy and Duncan 2002;Foody 2008;Iannella et al 2016Iannella et al , 2019aD'Alessandro et al 2018;Di Musciano et al 2020), and revealed interesting results especially when coupled with ecological modelling (Santos et al 2006;Iannella et al 2018;Cerasoli et al 2019;Iannella et al 2019b;Lepcha et al 2019) and remote sensing applications (Kerr and Ostrovsky 2003;Pettorelli et al 2014Pettorelli et al , 2016Wang and Gamon 2019).…”
Section: Introductionmentioning
confidence: 99%